Visible Spectrophotometric Methods for the Determination of Venlafaxine Hydrochloride and Ritodrine Hydrochloride in Pharmaceutical Formulations - GOWRI SANKAR, D.; SNEHALATHA, B.; VIJAYASRI, K.; MURTHY, T.K.; KUMAR, J.M.R.; REDDY, M.V.V.N. (Asian Journal of Chemistry, 2010)
Simple and sensitive visible spectrophotometric methods have been developed for the estimation of venlafaxine hydrochloride and ritodrine hydrochloride. In the proposed methods the drugs react with Folin-Ciocalteu reagent under alkaline conditions, which form blue-coloured chromogens having absorption maxima at 740 nm and 675 nm and obey Beer's law in the concentration ranges of 10-50 μg/mL and 2.5 to 12.5 μg/mL respectively. These methods are extended to pharmaceutical preparations and there is no interference from any common pharmaceutical additives and diluents.